The associations of positive and negative mental well-being with physical activity during the COVID-19 across late adulthood - Tiina Savikangas; Tiia Kekäläinen; Anna Tirkkonen; Sarianna Sipilä; Katja Kokko (BMC Public Health)
Abstract Background Mental well-being (MWB) may play an important role in physical activity (PA) behavior, but the independent associations of affective MWB indicators and depressive symptoms with PA are sparsely investigated in late adulthood. We investigated the associations of positive affect, negative affect, and depressive symptoms with PA during the COVID-19 restrictions across late adulthood. Methods Cross-sectional data came from two Finnish population-based studies. The younger cohort (N = 162, 56% women, 60–61 years) was drawn from the TRAILS study, and the older (N = 272, 60% women, 72–88 years) from the PASSWORD study. Data on PA frequency (1–7; from “not at all” to “approximately daily”) and perceived changes in PA (no change/increased/reduced) during COVID-19 restrictions were self-reported. MWB was assessed by positive and negative affect (International Positive and Negative Affect Schedule Short Form) and depressive symptoms (younger cohort: General Behavioral Inventory; older cohort: Geriatric Depression Scale). Associations between MWB and PA were analyzed using linear and multinominal logistic regression models. Results When each MWB indicator was investigated separately, higher positive affect was associated with higher PA frequency in both cohorts and with a higher likelihood of increased PA in the younger cohort; higher negative affect was associated with a higher likelihood of reduced PA in the older cohort; higher depressive symptoms were associated with lower PA frequency in both cohorts and with a higher likelihood of reduced PA in the older cohort (p ≤ 0.009 for all), In the final models including all three MWB indicators, socioeconomic, and health-related covariates, only the association between higher positive affect and higher odds of increased PA remained significant in the younger cohort (OR = 4.28, p = 0.006). In the older cohort, only the associations of higher depressive symptoms with lower PA frequency (β=-0.097, p = 0.024) and higher odds of reduced PA (OR = 1.26, p = 0.010) remained significant. Conclusions Positive affect was independently associated with increased PA during the COVID-19 restrictions in sixty-year-olds. Higher depressive symptoms were independently associated with lower PA frequency and a higher likelihood of reduced PA in 72-88-year-olds. Positive and negative aspects of MWB have different relations to PA among people aged 60 and 70 + when one’s daily routines are restricted. Trial registration number ISRCTN52388040 (the PASSWORD study).